Atypical Mycobacterial Infections After Plastic Surgery Procedures Abroad: A Multidisciplinary Algorithm for Diagnosis and Treatment. Issue 3 (March 2020) - Leto Barone, Angelo A.; Grzelak, Michael J.; Frost, Christopher; Ngaage, Ledibabari M.; Ge, Shealinna; Kolegraff, Keli; Chopra, Karan; Tornheim, Jeffrey A.; Caffrey, Julie; Lifchez, Scott D.; Rasko, Yvonne
Abstract : Background: The recent rise in medical tourism, especially for cosmetic procedures, has been mirrored by an increase in the incidence of infections with Mycobacterium abscessus, which is an atypical mycobacterium that is ubiquitous in aquatic environments. M. abscessus soft tissue infections arise from the use of improperly sterilized water and surgical equipment during surgical procedures, and these infections have devastating consequences if not promptly treated. M. abscessus infections are notoriously difficult to diagnose and properly treat, and therefore, we illustrate a typical case presentation and provide a comprehensive diagnostic and treatment algorithm. Methods: Of the patients who have presented to our hospital for treatment of cutaneous M. abscessus infections, a representative patient's story was included to illustrate the typical presentation and treatment timeline. The current literature on M. abscessus infections was reviewed, and this literature and the clinical experience of our plastic surgery and infectious disease teams were used in the creation of a diagnostic and treatment algorithm for M. abscessus infections. Results: M. abscessus infections can have an incubation period of months, and the classic presenting signs include purulent drainage, violaceous nodules, and subcutaneous abscesses at the site of a recent surgery. A key finding is persistence of the infection despite debridement and empiric antibiotic treatment. Cultures grown on mycobacterial-specific growth media are considered the diagnostic criterion standard, but high clinical suspicion is enough to warrant the initiation of treatment. Treatment itself consists of surgical drainage and debridement in combination with multidrug antibiotic regimens that typically include amikacin, a macrolide, and a carbapenem or cephalosporin antibiotic, with the option for macrolide and fluoroquinolone maintenance therapy. Conclusions: M. abscessus cutaneous infections present with unique history and physical examination findings and often require complex diagnostic workups and treatment plans. Increased provider awareness of the management and potential complications of M. abscessus is crucial to the improvement patient outcomes, as is a multidisciplinary approach that incorporates primary care providers, pathologists, plastic surgeons, and infectious disease specialists.